The Effect of Profitability, Capital Intensity, Company Size, Institutional Ownership, and Corporate Social Responsibility on Corporate Tax Avoidance - Monika Kussetya Ciptani; Happy Rizka Valentina Situmorang (Universitas Padjadjaran, 2023)
Tax-related state income plays a significant part in funding state spending. The government is working to maximize tax income, but tax avoidance practices have prevented it from reaching. The effective tax rate (ETR) was used in this study to calculate tax avoidance. This study aims to gather empirical data on the relationship between tax avoidance and variables such as profitability, capital intensity, company size, institutional ownership, and corporate social responsibility. This study was done at mining companies listed on the Indonesia Stock Exchange between 2017 and 2021. From the tax perspective, the mining industry contributes so much to the national economy that it receives comparatively little oversight, resulting in unethical behavior such as tax dodging. The discussion of tax avoidance is interesting because many mining companies still do tax avoidance, which will impact the interest of the government's development. Purposive sampling was used to determine the sample size, yielding 55 samples. Data were evaluated using multiple linear regression analysis with specific criteria, and up to 11 companies were found to fit the criteria. This study's results indicate that profitability positively affects tax avoidance, while capital intensity, company size, institutional ownership, and corporate social responsibility do not.